Penyuluhan Hipertensi Pada Lansia Desa Sido Rejo Kec Kabawetan Kab Kepahiang - Sari, Leka Julita; Sari, Ezi Maretta; Situmorang , Anggita; Fernandes , Brilian; Murwati, Murwati; Wulandari, Wulandari; Azissah, Danur; Rohani, Tuti (Jurnal Kewirausahaan & Inovasi, 2025)
Hypertension or high blood pressure is often referred to as The Silent Killer because it does not cause clear signs and symptoms unless it has entered the complication phase. Therefore, this disease can continue to get worse without being realized until it reaches a life-threatening level. Objective: At the end of the counseling process, all Kepahiang community members in Sido Rejo Village can understand and comprehend about hypertension. Methods: The method used in this counseling is by delivering material using leaflets. Results and discussion: The final result of this activity, extension workers are able to provide counseling material that has been made at least 90% of the counseling material.